Characteristics of confirmed COVID-19 patients receiving treatment at Sanglah hospital for January-February 2022 - Kusumawati, Novinna; Andikayasa, Pande Made; Aryanthana, Gede Oky; Rai, Ida Bagus Ngurah; Kusumawardhani, Ni Wayan Candrawati; Dwi, Ida Ayu Jasminarti; Eka Arisanti, Ni Luh Putu; Ketut Sajinadiyasa, I. Gede; Andrika, Putu (International Journal of Advances in Medicine, 2022)
Background: The ongoing mutation of the COVID-19 virus causes an increase in transmission and a decrease in vaccine effectiveness. COVID-19 cases since the end of 2021 have continued to increase, and data on the characteristics of patients with confirmed COVID-19 at Sanglah hospital for this period is not yet available. Therefore, this study aims to determine the characteristics of confirmed COVID-19 patients who received treatment at Sanglah hospital from January to February 2022. Methods: This study is a descriptive study using a cross-sectional approach taken from medical record data. Results: There were 276 COVID-19 patient subjects with an average age of 53 years, consisting of 51.1% male and 48.9% female. Most occupations are private employees, 29.0%. The 39.5% of patients had mild symptoms, and 5.8% had critical symptoms. Cough (51.8%) and fever (40.6%) were the main clinical symptoms, and chronic kidney disease was the most common comorbidity at 16.7%. As many as 46.0% of COVID-19 patients have received vaccines at least 2x, and 2.9% of patients are previous COVID-19 survivors. Conclusions: The characteristics of confirmed COVID-19 patients who received treatment at Sanglah hospital in January and February 2022 were more male than female, with the most jobs as private employees. Most patients have mild to moderate symptoms with a chief complaint of cough. Almost half of the patients have been vaccinated at least 2x. Most of them are not COVID-19 survivors.